Frecuencia de corte y niveles de fertilización en pasto Janeiro (Eriochloa polystachya Kunth) M2 irradiado a 52 Gy de rayos gamma, en el cantón Babahoyo - Mosquera Peralta, Jessica Marilyn (2020)
The experimental work was carried out on the grounds of the Faculty of Agricultural Sciences of the Technical University of Babahoyo, located at kilometer 7.5 of the Babahoyo - Montalvo road, located at a height of 8 masl at UTM X coordinates: 1.772 394 6 ; Y: 710 293, presents an average temperature of 24 - 26 ºC. The research had the general objective of evaluating the agronomic and productive response of the grassland irradiated at 52 Gy subjected to different levels of fertilization and cut frequencies, under Babahoyo conditions. Grass stolons were used. To obtain the results, the experimental design Completely Random Design (DCA) with a 5% statistical probability was used. According to the results, it was determined that for plant height, treatments 3 (0 Gy, 250 Kg of fertilizer and 35 days of cut) and 8 (52 Gy, 250 Kg of fertilizer and 45 days of cut) stood out with 2.77 m and the lowest value in treatments 1 (0 Gy, 0 Kg of fertilizer and 35 days of cut) and 6 (52 Gy, 0 Kg of fertilizer and 45 days of cut) with 1.49 m. Regarding stem diameter, a highly significant difference was recorded. The treatments were 7 (52 Gy, 250 Kg of fertilizer and 35 days of cut) and 8 (52 Gy, 250 Kg of fertilizer and 45 days of cut) with an average of 0.52 that presented the best results. Regarding number of clumps, treatment 2 (0 Gy, 0 Kg of fertilizer and 45 days of cut) with an average of 28.25 clumps, presented the highest value for this variable; the lowest value was for Treatment 6 (52 Gy, 0 Kg of fertilizer and 45 days of cut) with 24.5. Regarding the leaf width, it can be seen that treatment 8 (52 Gy, 250 Kg of fertilizer and 45 days of cutting) reached the widest leaf width with a value of 2.07 cm, the lowest value corresponded to the treatment 1 (0 Gy, 0 Kg of fertilizer and 35 days of cut) with a value of 1.34 cm. In the analysis of the variable % RMS, treatment 4 (0 Gy, 250 Kg of fertilizer and 45 days of cut) stood out with 33.60% and the lowest value is represented by treatment 5 (52 Gy, 0 Kg of fertilizer and 35 cut-off days) with 23.20%.